Determinants of Stunting in Children Aged 12 to 60 Months in Kota Waingapu District, East Nusa Tenggara, Indonesia - Manalu, Samuel Bungaran Partahi Saud; Eyanoer, Putri C (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Stunting is a problem that is often not recognized in the community because short stature is so common and often considered normal. In Indonesia, the incidence of stunting under five is a major nutritional problem, with an average prevalence from 2015-2017 of around 36.4%. This study aimed to investigate the determinants of stunting in children aged 12 months - 60 months in the Waingapu District.Subjects and Method: This was a cross-sectional study conducted at Posyandu, Waingapu District, in December 2020. A total of 105 samples were selected based on inclusion and exclusion criteria using non-probability consecutive sampling. The dependent variable was stunting. The independent variables were exclusive breastfeeding, birth weight, household income, maternal education, maternal nutritional status, and maternal age. The data were collected by questionnaire and analyzed by Chi-square.Results: The prevalence of stunting in children aged 12 to 60 months in the Waingapu District was 24.8%. The bivariate analysis elucidated that the incidence of stunting was significantly increased by poor maternal education (OR= 3.40; 95% CI= 1.29 to 8.97; p= 0.011), poor maternal nutritional status (OR= 3.06; 95% CI= 1.05 to 8.89; p= 0.034), and low household income (p = 0.002).Conclusion: Poor maternal education, poor maternal nutritional status, and low household income significantly increase the incidence of stunting.Keywords: stunting, determinant, nutritional status, childrenCorrespondence: Samuel Bungaran Partahi Saud Manalu. Faculty of Medicine, Universitas Sumatera Utara. Email: samuel.manalu.4th@gmail.comIndonesian Journal of Medicine (2021), 06(02): 220-229https://doi.org/10.26911/theijmed.2021.06.02.11